www.przekonajwyborcę.pl - technologie informacyjne w służbie polityki = www.przekonajwyborce.pl: information technologies in political service - Szaban, Dorota (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The process of implementing democratic rules of social and political life are accompanied by an information revolution. In election contests, politicians use new and new instruments of political marketing in search of effective ways of running political campaigns. One of the modern tools in the political struggle for the voter is the Internet.
Keywords: rewolucja informacyjna; wybory parlamentarne; internet; marketing wyborczy